Genealogia rodu Walewskich herbu Kolumna w XVII-XVIII w. - Kobierecki, Michał (Acta Universitatis Lodziensis. Folia Historica, 2001)
Recently several books have been published which deal with the history of the families of the Chodkiewicz, the Lanckorońscys from Brzeź, the Sapiehas, the Branickis or the Radziwiłłs. Family trees occupy the main place in these publications since for the well-known Polish families they were developed in the past and passed on from a generation to generation. However, the genealogy of noble families is difficult to be restored due to numerous difficulties as the information is largely dispersed. The Walewskis family of the emblem Kolumna have their own family archives collected and filed between 1897 and 1940 by Kazimierz Walewski in Tubądzin and it provides the documentation for the family tree. In 17th and 18th centuries the Walewskis accounted for 163 men and 165 women representing several family branches: in Walewice, Rusiec, Dziebędów, Charłupia Wielka, Rembieszew, Pstrykonie the Cracow and Wołyń branches and Alexander Walewski’s, the Warrant Officer 1st Clas of Piotrków. Nearly all of them were based in the area of the former region of Sieradz, on the border region of Łęczyca and Rawa (Walewice) and in the region of Cracow and in Wołyń. The Walewskis were proud of having 36 local civil servants including two Governors (Voivodes) of Łęczyca and Sieradz and many local higher rank officials - Senators (these were the most numerous) mostly in the areas of Spicymierz, Rozprza, Brzeziny, Inowłódz or Sieradz. Within two centuries they frequently occupied other position as chamberlains (five times), Warrant Officers (thirteen times), High Stewards (six times) or the positions in local courts as High Sheriffs or country judges (three times). As far as the assets are concerned the Walewskis could not be found among magnates but the real estates they owned allowed them to be politically active and gain prestige in their local communities. When we analyse the family links of the Walewskis emblem Kolumna, they usually did not enter into relationships with famous families of the Republic of Poland, except some occasions like the Koniecpolskis, the Lanckorońskis and the Lubomirskis, but with the representatives of medium or lower class nobles who inhabited the region of Sieradz and its neighbourhood.